2021
DOI: 10.1186/s12931-021-01887-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 and lockdowns on pulmonary embolism in hospitalized patients in France: a nationwide study

Abstract: Background This study assessed the impact of the COVID-19 epidemic on overall hospitalizations for pulmonary embolism (PE) in France in comparison with previous years, and by COVID-19 and non-COVID-19 status. Methods Hospitalization data (2017–2020) were extracted from the French National Discharge database (all public and private hospitals). We included all patients older than 18 years hospitalized during the 3 years and extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(39 reference statements)
1
6
1
2
Order By: Relevance
“…Notably, pulmonary embolism as cause of death increased also in patients without any mention of COVID-19 in the death certificate. These findings are similar to what reported by French authors concerning national emergency hospitalisations due to pulmonary embolism and in-hospital fatality in 2020 [13] . The recognition (or not) of COVID-19 as the cause of pulmonary embolism may have therapeutic consequences also concerning the length of anticoagulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, pulmonary embolism as cause of death increased also in patients without any mention of COVID-19 in the death certificate. These findings are similar to what reported by French authors concerning national emergency hospitalisations due to pulmonary embolism and in-hospital fatality in 2020 [13] . The recognition (or not) of COVID-19 as the cause of pulmonary embolism may have therapeutic consequences also concerning the length of anticoagulation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a broader and more aggressive use of pharmacological preventative measures for venous thromboembolism may have partly reduced this risk, as recently shown by trials conducted in the hospital and ambulatory setting [11] , [12] . One nationwide French study illustrated that the number of pulmonary embolism-related hospitalizations and in-hospital fatality increased in 2020, particularly during the COVID-19 waves [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Comparable results were found in Denmark, but were in contrast to findings from Spain, which found no difference between the groups [18]. Those differences might be explained by larger, unselected data set of nationwide data in Denmark and in our study [37]. In general, the higher rate of case-fatality in PE patients with COVID-19 have to be considered in the context of the haemodynamic effect of systemic inflammation.…”
Section: Discussioncontrasting
confidence: 76%
“…In this context, also numbers of PE-related deaths increased during the pandemic in several countries [6,37,38]. Our findings from Germany revealed no increase in the prevalence of PE between 2019 and 2020, but we did observe a slightly higher casefatality of PE in 2020 with seasonal characteristics following the pandemic waves; this is opposing to reports of Italy or France, but in line with nationwide data from Denmark [6,37,39]. However, considering PE patients with COVID-19-infection, case-fatality was dramatically increased in comparison to PE patients without COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A French nationwide study reported an increased number of patients hospitalized with pulmonary embolism in 2020, mainly linked to the covid-19 waves, in both patients with and without covid-19. 32 This increase was also observed in the United Kingdom, 33 but not in Denmark. 34 In the present study, the difference between the 2021 and 2020 periods mainly occurred in the first five months, and was concentrated in non-covid-19 patients.…”
Section: Pulmonary Embolismmentioning
confidence: 77%